2022
DOI: 10.1097/cce.0000000000000699
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein D Influences Mortality During Abdominal Sepsis by Facilitating Escherichia coli Colonization in the Gut

Abstract: OBJECTIVES: Determine the role of surfactant protein D (SPD) in sepsis. DESIGN: Murine in vivo study. SETTING: Research laboratory at an academic medical center. PATIENTS: SPD knockout (SPD−/−) and wild-type (SPD+/+) mice. INTERVENTIONS: SPD−/− and SPD+/+ mice were subjected to cecal ligation and puncture (CLP). After CLP, Escherichia coli bacteremia was assessed in both groups. Cecal contents from both groups were cultured to assess for colonization by E. coli. To control for parental effects on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Also, surfactant protein (PDB ID: 1PW9) is antimicrobial in nature and potentially inhibits cell proliferation of gram-negative bacteria by the action of improving cell membrane permeability [ 15 ]. Another study reported that the enteral surfactant protein D worsens mortality after CLP by enhancing bacterial colonization in the gut [ 28 ]. Lactobacillus bacterial protein (PDB ID: 4MKS) was found to be the primary cause of septic urinary infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, surfactant protein (PDB ID: 1PW9) is antimicrobial in nature and potentially inhibits cell proliferation of gram-negative bacteria by the action of improving cell membrane permeability [ 15 ]. Another study reported that the enteral surfactant protein D worsens mortality after CLP by enhancing bacterial colonization in the gut [ 28 ]. Lactobacillus bacterial protein (PDB ID: 4MKS) was found to be the primary cause of septic urinary infection [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cecal Ligation and Puncture (CLP). CLP was performed as previously described 99 . Briefly, after induction of anesthesia and analgesia with ketamine (85 mg/kg) and xylazine (34 mg/kg), mice were anesthetized, and a midline laparotomy was performed.…”
Section: Models Of Infectionmentioning
confidence: 99%